Melanoma trials that defined surgical management. Issue 1 (13th December 2021) - Faries, Mark B.
Abstract: Treatment of regional lymph nodes in melanoma has been controversial for more than a century. A series of clinical trials evaluating elective lymph node dissection and then sentinel lymph node biopsy have helped define the current standard of care. These trials resulted in increasingly selective application of surgical intervention for regional lymph nodes in melanoma. First by focusing on optimal candidates for elective lymph node dissection and then by identifying patients through sentinel lymph node biopsy. The current standard of sentinel lymph node biopsy for appropriately selected patients and nodal observation for many patients, even with involved sentinel nodes is both more accurate in staging and much less morbid than what came before.